2014
DOI: 10.3109/09553002.2014.887233
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hypothermia on radiation-induced micronuclei and delay of cell cycle progression in TK6 cells

Abstract: The protective effect of hypothermia observed at the level of cytogenetic damage was not due to a modulation of cell cycle progression. A possible alternative mechanism and experiments to test it are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…Irradiation of tardigrades at different temperatures did not influence survival rates but low temperature resulted in a delay by 12 to 24 hours in the effect of gamma radiation. Irradiation on ice is a common procedure in many experiments of mammalian cells in order to reduce activation of DNA repair, along with other cellular processes, during the radiation exposure [ 34 , 35 ]. Recent studies have also shown that dehydration and low temperatures (below freezing) can provide protection to radiation damage by reducing the diffusion of free radicals [ 36 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Irradiation of tardigrades at different temperatures did not influence survival rates but low temperature resulted in a delay by 12 to 24 hours in the effect of gamma radiation. Irradiation on ice is a common procedure in many experiments of mammalian cells in order to reduce activation of DNA repair, along with other cellular processes, during the radiation exposure [ 34 , 35 ]. Recent studies have also shown that dehydration and low temperatures (below freezing) can provide protection to radiation damage by reducing the diffusion of free radicals [ 36 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, Baird and colleagues showed that hypothermia (13 °C) postpones DNA damage repair in irradiated BJ-hTERT cells and protects against cell death [ 75 ]. By contrast, a series of studies investigating hypothermia-induced DNA damage in human peripheral blood lymphocytes [ 76 , 77 , 78 , 79 , 80 ] has suggested the possibility of DNA repair promotion that leads to a reduced transformation of DNA damage to chromosomal aberrations. Therefore, to our knowledge, hypothermia-induced modulations of DNA damage repair in vitro remain controversial.…”
Section: Impairment Of Radiation Damage Repair Under Hypothermic Cmentioning
confidence: 99%
“…During hibernation, a remarkable resistance against radiation damage has been observed which could be helpful to counteract the radiation load during spaceflights [ 14 , 116 ]. Hypothermic conditions in which core body temperature decreases well below 37 °C provide some protection against radiation-induced damage [ 14 , 62 ] independent of whether hypothermia is applied before, during, or shortly after irradiation of cultured cells [ 62 ]. It was hypothesized that radioprotection during torpor may be the result of tissue hypoxia due to vasoconstriction [ 116 ] and decreased free radical production [ 21 ] as well as synergistically by reduced MR and a shift from glycolysis to lipolysis mimicking conditions during fasting [ 15 ].…”
Section: Protective Effects Of Hypometabolismmentioning
confidence: 99%